Unbending mind: Individuals with hoarding disorder do not modify decision strategy in response to feedback under risk. (January 2018) - Pushkarskaya, Helen; Tolin, David F.; Henick, Daniel; Levy, Ifat; Pittenger, Christopher
Abstract: Cognitive-behavioral models of hoarding disorder emphasize impairments in information processing and decision making in the genesis of hoarding symptomology. We propose and test the novel hypothesis that individuals with hoarding are maladaptively biased towards a deliberative decision style. While deliberative strategies are often considered normative, they are not always adaptable to the limitations imposed by many real-world decision contexts. We examined decision-making patterns in 19 individuals with hoarding and 19 healthy controls, using a behavioral task that quantifies selection of decision strategies in a novel environment with known probabilities (risk) in response to feedback. Consistent with prior literature, we found that healthy individuals tend to explore different decision strategies in the beginning of the experiment, but later, in response to feedback, they shift towards a compound strategy that balances expected values and risks. In contrast, individuals with hoarding follow a simple, deliberative, risk-neutral, value-based strategy from the beginning to the end of the task, irrespective of the feedback. This seemingly rational approach was not ecologically rational : individuals with hoarding and healthy individuals earned about the same amount of money, but it took individuals with hoarding a lot longer to do it: additional cognitive costs did not lead to additional benefits. Highlights: Decision styles of HD and HC are contrasted during choices under risk with feedback. HC explore before switching to strategies that balance expected values and risks. HD do not explore and only use value-based strategy irrespective of the feedback. HD and HC earned the same amount of money, but HD deliberated longer. HD may be biased toward deliberative ecologically inefficient decision style.